Scalar Dark Matter Formation in Electron - Axion Like Collider - N.N, Xuan; V.T, Thang (International Journal of Advanced Engineering Research and Science, 2022)
The aim paper is devoted to study the interaction of axion like (ALPs) with fermions when expanding the standard model. The process of collider between axion-electron, which produce scalar dark matter and release electron has been studied. The scattering amplitude and cross section of this collision in the center of mass system (CMS) have been calculated by using Mandelstam variables and then plotted its dependence on scattering angle and energy.